6+(4+x)=(6+4)+x=

Simple and best practice solution for 6+(4+x)=(6+4)+x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(4+x)=(6+4)+x= equation:



6+(4+x)=(6+4)+x=
We move all terms to the left:
6+(4+x)-((6+4)+x)=0
We add all the numbers together, and all the variables
(x+4)-(10+x)+6=0
We get rid of parentheses
x-x+4-10+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2m^2+3m+4=0 | | 3x2−2x+5=−12 | | 4x-10+5x+5+4x-10+4x+15+4x+15=540 | | 3(4x+18)+4x=180 | | 28/x=17 | | 16=-5z+6z | | 11x+24=68 | | 11-0.2x=7 | | -4.5x=9 | | x+23=5x-5 | | −6x−7=29 | | 32=-3(8h-2) | | a-3.4=6 | | 1/2v+7=13 | | 140=x^2-10x+21 | | 8.2^y=64.5 | | -2v-7-6=22 | | 15x2x=145 | | 20^2+30x=0 | | 8z+7=9z+2 | | 1/5x-8=95 | | 4c^2-(9(4c-9))=0 | | 2/3c-12=84 | | 4c^2=9(4c-9) | | -2y+6=68 | | 3m+4=m+16 | | 3.6+m=11.2 | | 1.5x=16-2.5x | | 10x+10=2x+26 | | 4(2x-5)-8=20 | | 3(3x-4)=5x+28 | | 56=7•x |

Equations solver categories